DI-052 Stability study of ceftazidime mylan through use in the ambulatory treatment of cystic fibrosis. (14th February 2016) - Bourge, X; Pages, J; Carpentier, I; Locher, F; Terrier, A
Abstract : Background: There is a local network dedicated to patients suffering from cystic fibrosis that is willing to provide healthcare, especially continuous antibiotherapy at home. The antibiotics, delivered to patients in the Baxter infusion system (continuous/intermittent), are prepared at the hospital pharmacy for a maximum of 7 days' use. Because of continuous backorders from the GSK laboratory, the Fortum preparation often has to be switched to the ceftazidime mylan preparation. The regulatory aspects has led us to conduct a stability study as there are no studies in the literature that have validated the use of the generic drug compared with ceftazidime mylan. Purpose: The aim of the study was to establish the stability of ceftazidime mylan once reconstituted and filled in the Baxter infusion system. The stability study was conducted to closely match intended use by patients at home (storage, temperature management, administration). The final goals of the study were: allow the use of the Fortum generic, ceftazidime mylan, for 12 h continuous perfusion. compare with Fortum data Material and methods: Preparation, including reconstitution, filling and sealing of the antibiotics at a 5 mg/mL concentration into the Baxter system was done under aseptic conditions and stored at 4–8°C. In order to analyse drug activity, some aliquots were made following an experiment plan and frozen until analysis by HPLC. The analyses were performed at different times and days to ensure an optimal match with the condition of use at home. The experiment was planned over a 10 day conservation pattern. Results: The guidelines consider remaining activity of 90% for antibiotics as efficient. Our results showed that activity was 89–90% after 12 h of perfusion during the experimental process of 10 days. Conclusion: The kinetic profiles of ceftazidime mylan and the GSK Fortum were similar. We can conclude that the use of ceftazidime mylan is validated for intermittent/continuous administration. We may further investigate the possibility of improving drug stability with a better cooling chain at home. References and/or Acknowledgements: Guidelines-ystic fibrosis. No conflict of interest.